(untitled) (Security Dialogues, 2023)
The Russian invasion of Ukraine, which began at the end of February 2022, confirmedthe de facto impotence of the EU policy towards the Western Balkans. Only the reaffirmationof the United States of America and NATO’s roles in the Western Balkans after 2017 had asignificant impact on the situation in the region, as it had for the previous three decades. Theimportance of their roles was confirmed after the entry of Montenegro and North Macedoniainto NATO and the achievement of the Prespa Agreement (2018). However, there are stillessentially unresolved issues, such as the relations between Belgrade and Pristina (which arecurrently accelerating primarily due to the US), the internal reconfiguration of relations inBosnia and Herzegovina, and the gradual attempt to suppress the further growth of Russianinfluence in certain states of the region (it already has a strong influence in Serbia and theBiH entity, the Republic of Srpska). In this sense, the author emphasises that only after the additional integration of thecountries of the region with the European Union and NATO, which implies an acceleratedcontinuation of the EU enlargement process but also a strengthened open-door policy, canNATO additionally ensure peace in the Western Balkans, where there are still significantand visible consequences of post-Yugoslav wars and numerous problems, such as a lack ofthe rule of law, an insufficient fight against corruption, and cross-border crime. Therefore,the current moment, characterised and determined by Russia’s aggression against Ukraine,should ensure the acceleration of geopolitical responses related to the admission of thecountries of the Western Balkans to the European Union and also empower the real andpro-European capacities of existing forms of regional cooperation. The author emphasisesthe necessity of accelerated integration of the remaining WB entities into NATO, which theyhave already pursued.